The mental health of elite athletes: A narrative systematic review - Rice, S. M.; Purcell, R.; De Silva S.; Mawren, D.; McGorry, P. D.; Parker, A. G. (Sports Medicine, 2016)
Background: The physical impacts of elite sport participation have been well documented; however, there is comparatively less research on the mental health and psychological wellbeing of elite athletes. Objective: This review appraises the evidence base regarding the mental health and wellbeing of elite-level athletes, including the incidence and/or nature of mental ill-health and substance use. Methods: A systematic search of the PubMed, EMBASE, SPORTDiscus, PsycINFO, Cochrane and Google Scholar databases, up to and including May 2015, was conducted. Results: The search yielded a total of 2279 records. Following double screening, 60 studies were included. The findings suggested that elite athletes experience a broadly comparable risk of high-prevalence mental disorders (i.e. anxiety, depression) relative to the general population. Evidence regarding other mental health domains (i.e. eating disorders, substance use, stress and coping) is less consistent. These results are prefaced, however, by the outcome of the quality assessment of the included studies, which demonstrated that relatively few studies (25 %) were well reported or methodologically rigorous. Furthermore, there is a lack of intervention-based research on this topic. Conclusion: The evidence base regarding the mental health and wellbeing of elite athletes is limited by a paucity of high-quality, systematic studies. Nonetheless, the research demonstrates that this population is vulnerable to a range of mental health problems (including substance misuse), which may be related to both sporting factors (e.g. injury, overtraining and burnout) and non-sporting factors. More high-quality epidemiological and intervention studies are needed to inform optimal strategies to identify and respond to player mental health needs.